Crystal structure of a domain‐swapped photoactivatable sfGFP variant provides evidence for GFP folding pathway. (20th March 2019) - Kesgin‐Schaefer, Stephanie; Heidemann, Johannes; Puchert, Anke; Koelbel, Knut; Yorke, Briony A.; Huse, Nils; Pearson, Arwen R.; Uetrecht, Charlotte; Tidow, Henning
Abstract : Photoactivatable fluorescent proteins (PA‐FPs) are a powerful non‐invasive tool in high‐resolution live‐cell imaging. They can be converted from an inactive to an active form by light, enabling the spatial and temporal trafficking of proteins and cell dynamics. PA‐FPs have been previously generated by mutating selected residues in the chromophore or in its close proximity. A new strategy to generate PA‐FPs is the genetic incorporation of unnatural amino acids (UAAs) containing photocaged groups using unique suppressor tRNA/aminoacyl‐tRNA synthetase pairs. We set out to develop a photoactivatable GFP variant suitable for time‐resolved structural studies. Here, we report the crystal structure of superfolder GFP (sfGFP) containing the UAA ortho ‐nitrobenzyl‐tyrosine (ONBY) at position 66 and its spectroscopic characterization. Surprisingly, the crystal structure (to 2.7 Å resolution) reveals a dimeric domain‐swapped arrangement of sfGFP66ONBY with residues 1–142 of one molecule associating with residues 148–234 from another molecule. This unusual domain‐swapped structure supports a previously postulated GFP folding pathway that proceeds via an equilibrium intermediate. Abstract : A new strategy to generate photoactivatable fluorescent proteins for high‐resolution live‐cell imaging is the genetic incorporation of unnatural amino acids (UAAs) using unique suppressor tRNA/aminoacyl‐tRNA synthetase pairs. Surprisingly, the crystal structure of superfolder GFP containing the UAA ortho‐nitrobenzyl‐tyrosine at position 66 reveals a dimeric domain‐swapped arrangement supporting a previously postulated GFP folding pathway that proceeds via an equilibrium intermediate.